Human papillomavirus and p16 detection in cervical lymph node metastases from an unknown primary tumor - Park, Gi Cheol; Lee, Miji; Roh, Jong-Lyel; Yu, Myeong Sang; Choi, Seung-Ho; Nam, Soon Yuhl; Kim, Sang Yoon; Cho, Kyung-Ja (ELSEVIER SCIENCE BV, 2012)
Objectives: Human papillomavirus (HPV), a causative agent of oropharyngeal squamous cell carcinoma (SCC), may be detected in metastatic cervical lymph nodes (MCNs). We investigated whether HPV and p16 expression in MCNs can help identify oropharyngeal primaries in patients with cervical lymph node metastases from an unknown primary tumor (CUP) and predict their survival outcomes. Materials and methods: SCC MCNs of 58 patients with CUP were assayed for HPV by in situ hybridization and for p16 and p53 expression by immunohistochemistry. The presence of HPV and p16 in MCN was correlated with oropharyngeal tumor location and prognosis. Results: Oropharyngeal primaries were found in 20 patients. The sensitivity and negative predictive value (NPV) of HPV for oropharyngeal localization were 90.0% and 92.6%, respectively, and the sensitivity and NPV of p16 were 80.0% and 86.2%, respectively. Multivariate analyses showed that the location of the largest MCN (P = 0.035) and HPV (P = 0.004) were independent predictors of oropharyngeal tumors. Multivariate analyses showed that p16 expression was an independent predictor of disease-free survival (P = 0.030; hazard ratio (HR) = 0.286; 95% CI, 0.092-0.887) and that p53 expression (P = 0.017; HR = 3.154, 95% CI = 1.288-8.103) and extracapsular extension of MCN (P = 0.010; HR = 3.924, 95% CI = 1.387-11.097) were independent predictors of overall survival. Conclusion: Detection of HPV and p16 may help identify hidden oropharyngeal primaries in CUP patients and predict their survival outcomes. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: SQUAMOUS-CELL CARCINOMA; NECK-CANCER; OROPHARYNGEAL CANCER; GENE-PRODUCT; HPV-DNA; HEAD; EXPRESSION; PROGNOSIS; P53; SURVIVAL